Transformative Solar Panels: A Multidisciplinary Approach. (June 2013) - Sharif, Shani; Gentry, T. Russell; Yen, Jeannette; Goodman, Joseph N.
This paper focuses on the applications of geometrically transformable and expandable structures with deployed "energy production" mode and retracted "wind shedding" mode to replace the fixed photovoltaic (PV) panels and racking systems currently used in buildings rooftop installations. The significance of this expandable geometric system relies on its embedded motion grammar, i.e. rotation and translation transformations, in the system. The research draws inspiration from reconfiguration of compound tree leaves in nature, and addresses issues of redesign and modeling challenges that led to digital fabrication of the prototype. Finally, the research studies the development of a multidisciplinary research from the distributed cognition point of view, and emphasizes on the role of an iterative creation, sharing and reflection method for the development of a common ground for a successful collaboration.